2005
DOI: 10.1007/s10704-005-3073-1
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis of Fracture of Carbon Nanotubes Embedded in Composites

Abstract: Abstract. Due to the enormous difference in the scales involved in correlating the macroscopic properties with the micro-and nano-physical mechanisms of carbon nanotube-reinforced composites, multiscale mechanics analysis is of considerable interest. A hybrid atomistic/continuum mechanics method is established in the present paper to study the deformation and fracture behaviors of carbon nanotubes (CNTs) in composites. The unit cell containing a CNT embedded in a matrix is divided in three regions, which are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…[9][10][11][12][13] Most studies in the literature that focused on CNTs have considered only small-aspect ratio CNTs or a small number of interacting CNTs. In contrast, experiments have shown that single wall carbon nanotubes (SWNTs) can grow to lengths above 700 nm with a diameter of 0.9 nm, resulting in an aspect ratio as large as about 800.…”
Section: A Review: Modeling Of Mechanical Behavior Of Cntsmentioning
confidence: 99%
“…[9][10][11][12][13] Most studies in the literature that focused on CNTs have considered only small-aspect ratio CNTs or a small number of interacting CNTs. In contrast, experiments have shown that single wall carbon nanotubes (SWNTs) can grow to lengths above 700 nm with a diameter of 0.9 nm, resulting in an aspect ratio as large as about 800.…”
Section: A Review: Modeling Of Mechanical Behavior Of Cntsmentioning
confidence: 99%
“…Niaki et al [34] also simulated the fracture process of graphene sheet and SWNTs using a similar approach and reported that dynamic fracture stresses were, respectively, determined approximately 115 GPa and 122 GPa for different sizes of graphene sheet and armchair CNTs. A multiscale mechanics method used to study the deformation and fracture of CNTs embedded in a composite was presented by D. L. Shi et al [35], who reported that the critical strain of defect nucleation of a CNT is sensitive to its chiral angle, but not to its diameter and that the constraint effect of matrix makes the CNTs easier to fracture. They also simulated the effect of some other factors such as the waviness of CNTs, the CNT-matrix interface adhesion, and the distributed residual stresses in composites.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery in 1991 [1], carbon nanotubes (CNTs) have become a closely watched frontier in many scientific and technological fields due to their striking structure and superior mechanical, physical, and chemical properties [2][3][4][5][6][7][8][9]. They possess extremely high tensile Young's modulus of about 1 TPa or above, and chirality-dependent electrical conductivity [4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…They possess extremely high tensile Young's modulus of about 1 TPa or above, and chirality-dependent electrical conductivity [4][5][6][7][8][9][10][11][12][13][14]. Intramolecular junctions (IMJs), which seamlessly fuse two different CNTs together, have also been proposed to display a range of other interesting functions, different from the constituent CNTs [14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%